Prevention of Exposure Keratopathy with Sahaf Wet Chamber - Ch Javed iqbal, Farhan Ali, Imran Akram, Muhammad Sharjeel, Irfan Qayyum Malik (Pakistan Journal of Ophthalmology, 2015)
Purpose: To assess the efficacy of sahaf wet chamber in preventing exposure keratopathy in patients with lagophthalmos. Material and Methods: Seventy patients of lagophthalmos were included in the study from outdoor in ophthalmology department Mayo hospital, King Edward Medical University Lahore from 1st January 2013 to 31st December 2013 awaiting definitive surgical intervention. Sahaf wet chamber (transparent polyurethane dressing opsite with antibiotic ointment) were changed every 24 hours. The corneal flourescein stains were performed and exposure keratopathy assessed daily till the time of surgery. The criteria of efficacy was improvement or progression of exposure keratopathy. Results: None of 70 patients (0%) had progression of exposure keratopathy. The time on eye care every day was 3 min ± 1 min. Conclusion: Sahaf wet chamber is more effective, time saving, easy to apply and cost effective technique in reducing the incidence of corneal damage in patients with lagophthalmos awaiting definitive treatment. It can easily be done as an OPD procedure. Key Words: Exposure keratopathy, wet chamber, lagophthalmos